Viewing of 2-dimensional data - POHÁNKA, Vladimír (Contributions to Geophysics and Geodesy, 2021)
Advantages and disadvantages of the viewing of 2-dimensional data in the form of a text and an image are discussed and the new way of viewing combining the advantageous properties of these two ways is proposed. This way was realized by introducing a suitable data file format and by writing the programs for viewing and manipulating with the data.